2010
DOI: 10.1017/s0007485309990526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ground cover vegetation on the abundance and diversity of beneficial arthropods in citrus orchards

Abstract: The effect of ground cover upon the communities of beneficial arthropods established in the canopy of lemon trees was investigated, by comparing three ground-cover management treatments applied: RV, resident vegetation; S, sowed selected species; and BS, bare soil by controlling weeds with herbicide. Over two consecutive years, arthropod communities in the tree canopy were sampled periodically by beating and suction techniques. Significantly higher numbers of beneficial arthropods were found in the RV and S tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 41 publications
(64 reference statements)
3
36
0
3
Order By: Relevance
“…Thus, our first hypothesis based on the supposition that lacewings would find more complementary food from the many flowering weeds of the ground vegetation, which was supported on previous studies that found high abundance of many predatory insects at ground vegetation level (e.g., Bianchi et al 2006;Silva et al 2010) was wrong. There may be several reasons explaining this behavior: the comparative higher disturbance at the ground vegetation level (mowing, fruit picking, etc), the better refuge against wind and extreme temperatures that shelterbelts represent (wooded habitats provide more moderate microclimate (Forman and Baudry 1984)), and/or the higher abundance of non-flying competing predators in the above ground layer (some of them can act also as predators of lacewings).…”
Section: Insect Distribution Inside Organic Agroecosystemssupporting
confidence: 62%
“…Thus, our first hypothesis based on the supposition that lacewings would find more complementary food from the many flowering weeds of the ground vegetation, which was supported on previous studies that found high abundance of many predatory insects at ground vegetation level (e.g., Bianchi et al 2006;Silva et al 2010) was wrong. There may be several reasons explaining this behavior: the comparative higher disturbance at the ground vegetation level (mowing, fruit picking, etc), the better refuge against wind and extreme temperatures that shelterbelts represent (wooded habitats provide more moderate microclimate (Forman and Baudry 1984)), and/or the higher abundance of non-flying competing predators in the above ground layer (some of them can act also as predators of lacewings).…”
Section: Insect Distribution Inside Organic Agroecosystemssupporting
confidence: 62%
“…Weeds benefit different arthropods, providing habitat, additional sources of food (pollen and nectar), favorable microclimate for the development of natural enemies, parasitoids and other insects, shelter and refuge from predators and to overcome disturbances caused by agricultural practices (Jonsson et al, 2008;Silva et al, 2010). Natural enemies benefit from the resources available for these plants, which favors their efficiency as pest regulators (Landis et al, 2000).…”
Section: Weed Plants Are a Habitat For Natural Enemies In Agroecosystemsmentioning
confidence: 99%
“…These plants are a source of shelter, refuge, food and favorable microclimate for the development of different insects and breeding sites for predators and parasitoids (Steinbauer et al, 2006;Silva et al, 2010). However, weed control can alter the abundance and flora of different plant species, which can damage the associated arthropods (Landis et al, 2000;Albajes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Según estos autores el manejo del hábitat se puede abordar a nivel de la parcela, de la explotación o del paisaje. En los últimos años se ha publicado una gran cantidad de estudios sobre el papel que pueden cumplir los distintos componentes del sistema agrícola, tales como las cubiertas vegetales (Bugg y Waddington, 1994;Wyss et al, 1995;Sirrine et al, 2008;Gámez-Virués et al, 2009;Silva et al, 2010), los márgenes de los cultivos (Rieux et al, 1999;Holland y Fahrig, 2000;Olson y Wäckers, 2007), los corredores vegetales (Nicholls et al, 2001) y, en general, las denominadas áreas no cultivadas (Gurr et al, 2003;Boller et al, 2004;Bianchi et al, 2006). …”
Section: Manejo Del Sistema Como Instrumento Esencial En La Proteccióunclassified